Effect of fluoride-containing silicone samples on Streptococcus mutans - Mr Lingyu Zhang; Dr QINGYU WANG; Dr Qingyu Wang; Mr Yafei Hou; Professor Jing Zou (Elsevier, 2023)
Aim or Purpose: This study aimed to investigate the effects of silicone samples with different fluoride concentrations on the growth and biofilm formation of Streptococcus mutans (S. mutans). Materials and Methods: The experimental samples, with a diameter of 10 mm and a thickness of 2.5 mm, were prepared using mixtures of silicone and sodium fluoride with sodium fluoride concentrations of 0.5%, 1%, 1.5%, 2%, and 2.5%, respectively. The control group did not contain sodium fluoride. Each group had 6 pieces. All samples were immersed in 2 ml of deionized water with pH=7.0, and then the extract was added to S. mutans culture medium. Optical density values at 600 nm (OD600) at 5, 8, and 12 hours and 575 nm (OD575) at 4, 8, and 16 hours were measured to evaluate the growth and biofilm formation of S. mutans, respectively. Results: At all time-points, the OD600 value in all experimental groups were significantly lower compared to the control group (P<0.05). At 4 and 8 hours, the significant decrease in OD575 values were found between the 1.0%, 1.5%, 2.0%, and 2.5% groups and the control group (P<0.05). At 16 hours, compared to the control group, all experimental groups, including the 0.5% group, had significant inhibitory effects on the biofilm formation of S. mutans (P<0.05), however, the inhibitory effects between different experimental groups were similar. Conclusions: Fluoride-containing silicone samples had inhibitory effects on the growth of S. mutans and the formation of biofilms. Considering the safety of fluoride intake, it may be feasible to use 0.5% or lower concentrations to make fluoride-containing silicone orthodontic appliances.